2018
DOI: 10.1016/j.pedneo.2017.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of individual-level and community-level effects on childhood undernutrition in Malawi

Abstract: This study provides evidence of the importance of both individual- and community-level factors in determining childhood undernutrition. Interventions against childhood undernutrition should consider the various predictors discussed in this study in order to reduce undernutrition in children and contribute to their well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
92
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(117 citation statements)
references
References 31 publications
(57 reference statements)
20
92
2
3
Order By: Relevance
“…This finding is consistent with previous studies. 13,23,24 Male children are believed to be more physically active and to expand more energy that should have been channeled to increase growth. 20 This study further revealed that childhood stunting was inversely related to the maternal education level, which was in line with findings in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is consistent with previous studies. 13,23,24 Male children are believed to be more physically active and to expand more energy that should have been channeled to increase growth. 20 This study further revealed that childhood stunting was inversely related to the maternal education level, which was in line with findings in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…20 This study further revealed that childhood stunting was inversely related to the maternal education level, which was in line with findings in previous studies. 13,14,[23][24][25] Maternal education affects child nutrition via multiple pathways. Higher educational levels, for example, can be associated with higher knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Habyarimana () and Makoka () developed SLR model of child malnutrition and found child's sex and birth order and mother's education and body mass index (BMI) as potential factors of child malnutrition. Using GEE logistic model, Ntenda and Chuang () showed that children with a diarrhoeal episode in the last 2 weeks, having a poorly educated mothers, belonging to a low socio‐economic household, and living in communities with low female educational attainment are more likely to be malnourished in Malawi. Islam et al () also used GEE model to show that household with poor asset index, being a male child, and child age are the risk factors of stunting for 12‐ to 24‐month children.…”
Section: Introductionmentioning
confidence: 99%
“…The community characteristics were not derived directly from the respondents but derived by aggregating relevant individual response at the cluster level and dividing the resulting distribution into two or three equal parts. This method has been widely used in deriving community characteristics from the Demographic and Health Survey (DHS) data [43][44]. Table 1 provides more information on the research variables.…”
Section: Explanatory Variablesmentioning
confidence: 99%